1990
DOI: 10.1159/000185937
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Left Ventricular Hypertrophy in Dialysis Patients

Abstract: To determine the clinical and echocardiographic outcome of left ventricular hypertrophy a prospective study was undertaken of 104 nondiabetic dialysis patients without dilated cardiomyopathy, who were followed for 3–5 years. 33% of patients had normal echocardiogram, 41% mild and 21% severe hypertrophy (left ventricular wall thickness > 1.4 cm in diastole). In the first 2 groups 16%o progressed to severe hypertrophy, 23% were admitted with congestive heart failure after starting dialysis therapy, and 2-year cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 18 publications
5
85
0
Order By: Relevance
“…Different studies in secondary hypertension found that the presence of LV hypertrophy predicted death in hypertensive patients with end-stage renal disease independent of other factors. [53][54][55] An increased risk for cardiovascular morbid events in patients suffering from coronary artery disease has also been related to the presence of LV hypertrophy. The survival rate in patients with coronary heart disease and LV hypertrophy was decreased compared with the survival rate in those with no evidence of LV hypertrophy.…”
Section: Prognosis Of Left Ventricular Hypertrophymentioning
confidence: 99%
“…Different studies in secondary hypertension found that the presence of LV hypertrophy predicted death in hypertensive patients with end-stage renal disease independent of other factors. [53][54][55] An increased risk for cardiovascular morbid events in patients suffering from coronary artery disease has also been related to the presence of LV hypertrophy. The survival rate in patients with coronary heart disease and LV hypertrophy was decreased compared with the survival rate in those with no evidence of LV hypertrophy.…”
Section: Prognosis Of Left Ventricular Hypertrophymentioning
confidence: 99%
“…[1][2][3] During the conservative management of patients undergoing maintenance hemodialysis (MHD), the decrease of the glomerular filtration rate (GFR) was associated with left ventricular hypertrophy (LVH). [4][5][6][7] The presence of LVH, in turn, constitutes an important independent factor of cardiovascular risk in patients with chronic kidney disease (CKD), including MHD patients. Both LVH and systolic dysfunction have major contributions to this increased risk of cardiovascular death.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship, however, between hypertension and LVH is not so clear in uremia. Whereas some studies showed that prolonged control of hypertension in dialysis patients significantly decreased left ventricular mass (Cannella et al, 1993;Klingbeil et al, 2000), other studies showed that LVH did not change (London et al, 1990;London et al, 1994) or could even progress (Huting et al, 1988;Parfrey et al, 1990) in spite of adequate blood pressure control in uremic patients. Anemia is another common complication in uremia and may also contribute to the pathogenesis of LVH because it is associated with a high output state placing the left ventricle at risk for failure.…”
Section: Introductionmentioning
confidence: 99%